Family Problems in Marriage Law - Fitri, Diva Aidilla; Fitrianto, Bambang; Siregar, Rahman Maulana (Bacarita Law Journal, 2025)
Marriage is a legal bond regulated in Law Number 1 of 1974 concerning Marriage, which aims to create a harmonious and prosperous family. However, in practice, divorce still occurs frequently, including in Stabat Religious Court Decision Number 1113/Pdt.G/2023/PA.Stb. The main problem in this study is how the regulation of marriage law in Indonesia regulates divorce and the main factors that cause divorce in these cases. This research aims to analyze the regulation of divorce in Indonesia and identify the main causes of divorce based on a case study at the Stabat Religious Court. The research method used is normative juridical, with a legislative approach and case studies of court decisions. The results showed that divorce in Indonesia must go through the courts in accordance with Article 39 of the Marriage Law, with reasons regulated in Government Regulation No. 9 of 1975, such as prolonged disputes and domestic violence. In the case of the Stabat Religious Court Decision, the main factors for divorce are disharmony, unresolved arguments, and differences in principles that cause the relationship between husband and wife to be untenable. In conclusion, divorce is the last resort in resolving household conflicts that can no longer be saved. Therefore, there is a need for more effective mediation efforts and legal education to married couples so that they can understand the legal consequences of divorce before filing it with the court.